A Management Exhibition as a Platform for Student Edupreneurship in Innovation Based on Local Potential - Krido Eko Cahyono; Muhammad Yusron Assyadhili; Jesika Alifian; Allen Pranata Putra; Rizky Dermawan (Pelayanan Unggulan : Jurnal Pengabdian Masyarakat Terapan, 2026)
This community engagement initiative was prompted by students’ limited understanding of how to package local content into educational products with economic value, as well as the suboptimal integration of entrepreneurial values into teaching. The aim of this initiative is to foster an entrepreneurial spirit among students through edupreneurship, developed in the form of an exhibition based on local product. The method employed was the Participatory Action Research (PAR) approach, which involved students as active participants in the training, production, and marketing of local products, as well as in the organisation of the exhibition. The activity began with training on the basic concepts of edupreneurship, product packaging, and marketing strategies. The exhibition showcased various creative products such as food & beverage, eco bodycare, eco living style, and fashion accesories featuring local product motifs. This activity successfully enhanced students’ capacity for critical thinking, innovation, and productive collaboration. An entrepreneurship talk show held concurrently further strengthened students’ motivation and entrepreneurial insights. The results of the activity demonstrated that the management exhibition effectively served as a medium for transforming local product such as food & beverage, eco bodycare, ecoliving style, fashion accesories learning into a contextual, practical, and economically valuable experience through the edupreneurship approach.